ANALISA DAN PERANCANGAN SISTEM INFORMASI TICKETING HELPDESK ONLINE BERBASIS WEB: STUDI KASUS PT XYZ - Weli Likhar; Hari Purwanto (Fakultas Ilmu Komputer dan Desain - Unsurya, 2021)
AbstractionIn this research a web-based online helpdesk application system was developed, at PT.XYZ, currently if there are problems with work tools such as computers and other hardware at the office or in branch stores they must do manual reporting such as telephone and whatsapp. With such problems created a Web-based Ticketing Helpdeks System application development to facilitate these problems. The research methods used include analytical methods (field studies and literature studies) and application program design methods using SDLC. Based on the results of research at PT. , it can be identified that the control system for complaints that are reported cannot be done quickly because there is no ticket or work scheduling system. Ticketing Helpdesk System helps each department and branch store to report damage to computers, other hardware. The software used is Notepad ++, MySQL and PHP. So after the existence of this website, it is hoped that it can help each complaint be carried out effectively and efficiently.Â Keywords: PHP, MySQL, Ticketing System Helpdesk